Micro-enterprise and personalisation : what size is good care? - Needham, Catherine, 1974-; Allen, Kerry; Hall, Kelly (Social policy lecturer) (Policy Press, 2017)
Social service agencies in the United Kingdom are increasingly under pressure to provide personalized care, even as the larger climate of austerity puts pressure on their resources. Increasingly, this means that community-based organizations of five or fewer staff members - known as microenterprises - are being asked to handle work that was formerly the province of much larger providers. In part, this is rooted in the assumption that small organizations can be more innovative and responsive. This book tests that assumption, analyzing the work of care organizations with a specific focus on size and how it affects personalization and the quality of care.